The disclosure and assurance of corporate social responsibility a growing market (Cambridge Scholars Publishing, 2019)
The essays collected here specifically examine the new trends of sustainability performance and reporting. They provide theoretical argumentation and evidence about sustainability performance, and determinants of its voluntary disclosure and external assurance. The book will interest companies, managers, shareholders, stakeholders and public bodies directly related to sustainability performance, the voluntary disclosure of sustainability information, and the adoption of an external assurance process.